2019
DOI: 10.1080/0142159x.2019.1687865
|View full text |Cite
|
Sign up to set email alerts
|

The escape room as evaluation method: A qualitative study of nursing students’ experiences

Abstract: Purpose: Gamification or learning using game elements is a process that seeks to capture students' interest. One of the most popular games in recent years is the Escape Room, but the study of its use in education and with health professionals is still limited. The aim of this study was to find out the perceptions and experiences of final year nursing students in an Objective Structured Clinical Examination (OSCE) by means of an Escape Room.Methods: In January 2019, 9 focus groups (FG) were held, with a total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 29 publications
(53 reference statements)
4
24
0
1
Order By: Relevance
“…Some authors have reported a successful use of educational escape rooms in a wide variety of topics such as in nursery [7,8], pharmacy [9], psychology [10], telecommunications [11], and STEM courses [12][13][14] or climate change education [15]. However, most of the authors do not provide evidence of a learning process during educational escape room (EER) experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have reported a successful use of educational escape rooms in a wide variety of topics such as in nursery [7,8], pharmacy [9], psychology [10], telecommunications [11], and STEM courses [12][13][14] or climate change education [15]. However, most of the authors do not provide evidence of a learning process during educational escape room (EER) experiences.…”
Section: Introductionmentioning
confidence: 99%
“…The above suggestions challenge a fairly common initiative in that different quotations from several informants should be presented to support each category/theme in particular. For example, while suggesting that their study was situated within the socialist-constructivist paradigm, Heery et al (2019) propose that verbatim quotes enhanced the confirmability of the findings, whereas Roman et al (2020) indicate that, in their phenomenological study, "each of the main themes was defined and illustrated with representative quotes from the participants" (p. 405). McPeake et al (2020), on the other hand, conducted a qualitative inquiry analyzed with thematic content analysis and inserted "extracted quotations to support the thematic analysis" (p. 3).…”
Section: Discussionmentioning
confidence: 99%
“…As discussed in healthcare simulation best practices, simulation activities should include a custom prebriefing and debriefing/feedback for improvement of learning, as well as, the other elements of simulation design, based on the objectives (Diaz et al, 2020; INACSL Standards Committee, 2016; Robertiello et al, 2019). A healthcare simulation escape room should include these components and be clinically focused (Backhouse & Malik, 2019; Friedrich et al, 2020; Laerdal, n.d.a; Roman et al, 2020), such as, utilizing a high-fidelity patient simulator with content and/or skills. The ultimate goal of all healthcare simulation escape rooms should center around patient safety through improved participant, team, and/or patient outcomes, with a pressured timed response (Baily, 2020; Jaramillo Rincón & Trujillo Mejia, 2020; Laerdal, n.d.a).…”
Section: Discussionmentioning
confidence: 99%
“…In general, for education, an escape room is a teaching tool or activity wherein puzzle rooms are utilized for learning and/or engagement (Aubeux et al, 2020; Backhouse & Malik, 2019; Baily, 2020; Booker & Nestor, 2020; Brown et al, 2019; Connelly et al, 2018; Diaz et al, 2020; Diemer et al, 2019; Dietrich, 2018; Edwards et al, 2019; Fotaris & Mastoras, 2019; Friedrich et al, 2020; Jaramillo Rincón & Trujillo Mejia, 2020; Kinio et al, 2019; Kutzin, 2019; Laerdal, n.d.a; Nicholson, 2018; Reade, 2017; Robertiello et al, 2019; Roman et al, 2020; Terrasi et al, 2019; Wilby & Kremer, 2020). A theme may be incorporated or described (Aubeux et al, 2020; Brown et al, 2019; Connelly et al, 2018; Diaz et al, 2020; Dietrich, 2018; Kinio et al, 2018; Reade, 2017; Wilby & Kremer, 2020).…”
Section: Escape Room Descriptions/characteristicsmentioning
confidence: 99%
See 1 more Smart Citation